Determinants of financial deepening in Mexico: A dynamic panel data approach; Determinantes de la profundad financiera en México: Un enfoque de datos de panel dinámico - Isela Elizabeth Téllez-León; Francisco Venegas-Martínez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2019)
This paper aims to study the determinants of financial deepening (FD) in Mexico. FD is measured as the fraction of total credit assigned to private sector as a proportion of GDP. The explanatory variables include: enforcing contracts (rule of law) and institutions; bank regulation; bank competition; formal labor; and financial literacy, among others. The data contains information of each State of the Mexican Republic. The model estimation is performed by using ordinary least squares (OLS), robust least square (RLS) with several weights functions (to deal with outliers), and a dynamic panel model (DPM) estimated with the generalized method of moments (GMM). The main findings are that: 1) the rule of law, 2) financial savings, and 3) financial education are the main determinants of financial deepening in Mexico.
Keywords: G00; C5; G38; 330; Financial deepening; factors affecting financial deepening; econometric modeling; Mexico